Operationalizing inclusive innovation: Lessons from innovation platforms in livestock value chains in India and Mozambique - Swaans, Cornelis P.M.; Boogaard, Birgit K.; Bendapudi, R.; Taye, H.; Hendrickx, Saskia C.J.; Klerkx, Laurens (International Livestock Research Institute, 2013)
Various authors have identified the potential relevance of innovation system approaches for inclusive innovation, i.e. the means by which new goods and services are developed for and by the poor. However, it is still a question how best to operationalize this. Innovation platforms are a way of operationalizing interaction and learning among actors, and enable reshaping of relations and institutions. This paper explores the formation and functioning of innovation platforms with the aim to provide lessons on the conditions and factors that play a role in making them effective; it draws on a small-ruminant value chain project in India and Mozambique, making use of document review, detailed process reports, outcome mapping, and project team reflections. In addition to various structure and process components of inclusive innovation known from the literature, the study shows the importance of social organization, representation, and incentives to ensure a ‘true’ participatory innovation process, which is based on demand and embedded in the context; incremental change through so-called innovation bundles (i.e. combination of technical, organizational and institutional innovations) and reflexive learning (systematically challenging constraining factors) are critical to this. Furthermore, local institutions embedded in norms and values were crucial to understand people’s decisions. Due to weak linkages between value chain actors, (external) innovation brokers have a vital role to play to facilitate the innovation process. Overall, innovation platforms are a promising model for inclusive innovation, but they require a careful assessment of and adjustment to the (institutional) context.